LINGUOCULTURAL STUDY OF REALIAS IN THE FRENCH LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the concept of realia in the French language from a linguocultural perspective. Realia are culture-specific lexical units that reflect the unique social, historical, and cultural features of a particular nation. The study focuses on the classification, semantic characteristics, translation challenges, and cultural significance of French realias. Special attention is given to how these linguistic elements embody French identity, traditions, and worldview. The research also highlights the importance of realias in intercultural communication and language teaching.